The effectiveness of Woolwich massage on the smooth flow of breast milk in postpartum mothers in the Kampung Melayu sub-district, Bengkulu City. - Dhevia Hilmana Sukma; Rukmaini; Shinta Novelia (International Journal of Midwifery and Health Sciences, 2026)
Background Smooth breast milk flow is an important factor in successful breastfeeding during the postpartum period, but in the early days after delivery, some postpartum mothers experience difficulty in breast milk flow due to lack of breast stimulation and inhibition of the oxytocin reflex. One non-pharmacological effort that can be done to increase the smoothness of breast milk flow is Woolwich Massage, a breast massage technique that aims to stimulate the milk ejection reflex. The purpose of this study was to determine the effect of Woolwich Massage on the smoothness of breast milk flow and the differences between the intervention group and the control group in postpartum mothers in PMB in the Kampung Melayu District, Bengkulu City. The quasi-experimental design method with a post-test only approach with a control group in 30 postpartum mothers who were divided into an intervention group and a control group. The intervention group was given Woolwich Massage for three consecutive days, while the control group was not given any intervention, then the smoothness of breast milk flow was measured on the 7th day using an observation sheet. Data were analyzed using the Mann–Whitney test. The results of the study showed that the mean rank value of smoothness of breast milk release in the intervention group was 19.33 higher than the control group of 11.67, with a p value = 0.013 (p < 0.05), which indicates a significant difference between the two groups. The conclusion of this study is that Woolwich Massage has a significant effect on smoothness of breast milk release in postpartum mothers and is proven to be more effective than without intervention and can be considered as one of the non-pharmacological interventions in midwifery services, especially in postpartum maternal care, to help improve smoothness of breast milk release.